Effect Of Integrated Nutrient Management In Soybean Variety Tarkari Bhatmas-1 At Khumaltar Condition - Neupane, Reshama; Amgain, R.; Shrestha, R. (Agronomy Journal of Nepal, 2021)
Soybean (Glycine max L. Merril) is an important summer legume in terms of area and production in Nepal. A field experiment was conducted on the farm of National Agronomy Research Centre, Khumaltar, Lalitpur to evaluate the effect of different combination of nutrients on yield and yield component of soybean variety Tarkari Bhatamas-1. The experiment was laid out in a Randomized Complete Block Design (RCBD) consisting of eight nutrient treatments. These were 30:60:30 N:P2O5:K2O kg/ha (recommended dose), 30:80:30 N:P2O5:K2O kg/ha, 50:60:30 N:P2O5:K2O kg/ha, 50:80:30 N:P2O5:K2O kg/ha, 30:60:30 N:P2O5:K2O kg/ha + compost 10 ton/ha, 30:60:30 N:P2O5:K2O kg/ha + Rhizobium inoculation, 30:60:30 N:P2O5:K2O kg/ha + Biochar (@ 330 g/plot and Compost 20 t/ha with four replications. Results of the pooled analysis revealed that maximum grain yield (2258 kg/ha) and straw dry matter (2735 kg/ha) was obtained with the application of compost 20 t/ha followed by 30:60:30 N:P2O5:K2O kg/ha + compost 10 t/ha (2007 kg/ha) and straw dry matter (2394 kg/ha). The number of nodule and nodule dry weight was not affected by different nutrient combination. The number of pods significantly differed with nutrient combinations. The three years result suggested that 20-ton compost/ha or integration of recommended dose of chemical fertilizer with 10-ton compost/ha had shown the best treatment combination for the sustainable production of soybean at Khumaltar condition.